Strong enhancement of cyanine dye aggregation by a cationic surfactant - Guralchuk, G.Ya.; Katrunov, I.K.; Grinyov, R.S.; Sorokin, A.V.; Efimova, S.L.; Malyukin, Yu.V.; Yarmoluk, S.M. (Functional Materials, 2007)
Optical spectroscopy methods have been used to study the features of cyanine dye 3,3'-dimethyl-9-thienyl-thiacarbocyanine iodide (L-21) aggregation in the presence of cationic surfactant CPB at concentrations above the critical micelle concentration. It has been revealed that the addition of CPB promotes the formation of luminescent molecular aggregates. The aggregates have a complex structure that is manifested in the absorption spectrum as two new bands (hypsochromically and bathochromically shifted). The aggregates formed reveal a highly ordered structure and a significant luminescence.